Manajemen nyeri neuropati pada pasien diabetes melitus tipe 2: Studi literatur - Sandra Pebrianti; Bambang Aditya Nugraha; Iwan Shalahuddin (Holistik Jurnal Kesehatan, 2020)
Management of neuropathic pain in patients with diabetes mellitus patients type 2: A literature studyBackground: An increase in the population of people with diabetes mellitus (DM), has an impact on increasing the most serious complications of diabetic neuropathy. Studies reveal that 16% to 26% of patients with diabetes neuropathy experience pain. People with DM who experience diabetic neuropathy pain will feel very uncomfortable and disturbed, neuropathic pain causes complaints not only physically, but also the mood and quality of life of patients. Therefore, it is important to identify the management of neuropathic pain in patients with type 2 diabetes mellitus to improve the quality of life of patients.Purpose: This literature review is to identify the management of neuropathic pain in type 2 DM patients.Method: Tracking this literature review using databases such as Google Scholar, Pubmed and Proquest with inclusion criteria that focus on the management of neuropathic pain in DM patients, publication years between 2010-2020 in Indonesian and English, quasi experiment design and Randomized controlled trial . Obtained as many as 87 articles, 32 met the criteria of the year and as many as 19 were the last complete articles found as many as 10 articles which were in line with the focus of the search.Results: Neuropathy management interventions were grouped into exercise, relaxation distraction techniques, percutaneous electrical stimulation and supportive education.Conclusion: Exercise, relaxation distraction techniques, percutaneous electrical stimulation and educational supportive interventions become one of the interventions that can be considered to use in the management of neuropathic pain in type 2 diabetes mellitus patients to improve comfort and quality of life.Keyword: Management; Neuropathic Pain; Patients; Diabetes mellitus type 2Pendahuluan: Peningkatan populasi penyandang diabetes melitus (DM), berdampak pada peningkatan komplikasi yang paling serius yaitu neuropati diabetik.  Studi mengungkapkan bahwa 16% hingga 26% pasien dengan neuropati diabetes mengalami rasa nyeri. Penyandang DM yang mengalami nyeri neuropati diabetik akan merasa sangat tidak nyaman dan terganggu, nyeri neuropati menimbulkan keluhan tidak hanya fisik, namun juga mood dan kualitas hidup pasien. Oleh karena itu, menjadi penting untuk mengidentifikasi manajemen nyeri neuropati pada psien diabetes mellitus tipe 2 untuk meningkatkan kualitas hidup pasien.Tujuan: Dengan studi literatur untuk mengidentifikasi manajemen nyeri neuropati pada pasien DM tipe 2.Metode: Penelusuran dengan menggunakan basis data seperti google scholar, Pubmed dan Proquest dengan kriteria inklusi yang berfokus pada manajemen nyeri neuropati pada pasien DM, tahun publikasi antara 2010-2020 dalam bahasa Indonesia dan bahasa inggris, desain quasi experiment dan Randomized controlled trial. Didapatkan sebanyak 87 artikel, 32 memenuhi kriteria tahun dan sebanyak 19 merupakan artikel lengkap terakhir ditemukan sebanyak 10 artikel yang sesui fokus pencarian.Hasil: Intervensi manajemen neuropati dikelompokan menjadi exercise, teknik distraksi relaksasi, stimulasi listrik perkutan dan suportif edukatif.Simpulan: Exercise, tekhnik distraksi relaksasi, stimulasi listrik perkutan dan intervensi suportif edukatif menjadi salah satu intervensi yang dapat dipertimbangkan untuk digunakan pada manajemen nyeri neuropati pada pasien diabetes mellitus tipe 2 demi meningkatkan kenyamanan dan kualitas hidup.